EXPLORING THE IMPACT OF COMPETENCE, EDUCATION, AND WORK DISCIPLINE ON EMPLOYEE PRODUCTIVITY IN FINANCIAL INSTITUTIONS AND ASSET MANAGEMENT: A QUANTITATIVE ANALYSIS - Arie Armawan; Ellin Herlina (PT. Berkah Digital Teknologi, 2023)
Purpose: This study aims to determine the effect of Competence, Education and Work Discipline on the Productivity of Employees of Financial Institutions and Regional Assets in Cirebon RegencyResearch Methodology: This research uses a survey method. The survey method is used to solve actual large-scale issue problems with very large populations, so a large sample size is required.Results: There is a partial influence of competence on the productivity of Regional Financial and Asset Agency Employees in Cirebon Regency. There is a partial effect of education on the productivity of employees of the Cirebon Regency Regional Finance and Assets Agency. There is a partial influence of Discipline on the productivity of Employees of the Cirebon Regency Regional Financial and Asset Management Agency. There is a simultaneous influence of Competence, Education and Work Discipline on the productivity of Employees of the Regional Financial and Asset Management Agency in Cirebon Regency.Limitations: this research is not free from limitations, namely the object of research only focuses on Regional Financial Institutions and Assets in Cirebon Regency.